Role of epigallocatechin-3-gallate from green tea in iron chelation and endoplasmic reticulum stress pathway in colorectal cancer cells - Md Nesran, Zarith Nameyra (2018)
CRC is ranked at the third place in the list of most common malignant disease in the world. However, common treatments like radiotherapy and chemotherapy will cause physical side effects to the patients such as hair loss, nausea, burnt effects on skin, loss of appetite and many others. Based on the major scientific findings, epigallocatechin- 3-gallate (EGCG) is the most bioactive compound in green tea that is responsible for all its health benefits. Hence, this study intends to find out the roles of EGCG when targeting iron chelation and endoplasmic reticulum (ER) stress pathway in CRC. MTT assay was first performed involving colorectal cancer cell line (HT-29) and normal cell line which was embryonic fibroblast (3T3). Protein extraction and Western blot were done to observe the related proteins expression. Caspase 3/7 assay was also performed to determine apoptosis process induced by EGCG treatment. Desferrioxamine (DFO) has been used as a positive control throughout the experiment. From the MTT assay results, EGCG showed toxicity towards HT-29 at all incubationtimes. The IC50 values obtained were 262.5 μM, 190.3 μM and 88.1 μM at 24h, 48h and 72h incubation times respectively. However, EGCG was not toxic on 3T3. EGCG had up-regulated transferrin (TfR) (p < 0.01) protein and down-regulated ferritin-H (FtH) (p < 0.001) protein indicating that iron chelation activity has occurred in HT-29. EGCG also had induced ER stress in HT-29 by up-regulating proteins like immunoglobulin-binding (BiP) (p < 0.001), (PKR)-like endoplasmic reticulum kinase (PERK) (p < 0.01), eukaryotic initiation factor 2 alpha subunit (eIF2α) (p < 0.001), peIF2α (p < 0.01), activating transcription 4 (ATF4) (p < 0.01) and inositol requiring kinase 1 alpha (IRE1α) (p < 0.01). However, EGCG did not affect activating transcription factor 6 protein (ATF6) (p > 0.05). Due to iron chelation activity by EGCG, this has caused iron depletion and generation of reactive oxygen species (ROS) in the HT-29 cells. Subsequently, ER stress will be induced due to these causes and unfolded protein response (UPR) will be activated, resulting in apoptosis to occur. In conclusion, EGCG is a potential compound to treat CRC by targeting iron chelation and ER stress pathway.